Temporarily Quiescent Galaxies at Cosmic Dawn: Probing Bursty Star Formation - Viola Gelli; Andrea Pallottini; Stefania Salvadori; Andrea Ferrara; Charlotte Mason; Stefano Carniani; Michele Ginolfi (The Astrophysical Journal)
The bursty, time-variable nature of star formation in the first billion years, as revealed by JWST, drives phases of temporary quiescence in low-mass galaxies that quench after starbursts. These galaxies provide unique probes of the burstiness of early star formation and its underlying physical processes. Using the serra cosmological zoom-in simulations, we analyze over 200 galaxies with M _⋆ < 10 ^9.5 M _⊙ at z ∼ 6–8, finding that most experience quiescent phases driven by stellar feedback, with minimal influence from environmental effects. The fraction of temporarily quiescent galaxies increases with decreasing mass and luminosity, representing the dominant population at M _⋆ < 10 ^8 M _⊙ and M _UV > −17. By forward modeling their spectral energy distributions, we show that they are faint (〈 M _UV 〉 = −15.6 for M _⋆ = 10 ^8 M _⊙ ), have strong Balmer breaks (>0.5), and no emission lines. Comparing our predicted fractions with JWST results, we find similar luminosity-dependent trends; however, the observed fractions of temporarily quiescent galaxies at M _UV ∼ −20 to −19 are higher, suggesting that stronger feedback or additional mechanisms beyond supernovae may be at play. We propose searching for F200W dropouts and satellites in the proximity (<5″) of massive (>10 ^10 M _⊙ ) galaxies as effective strategies to uncover the hidden majority of faint ( M _UV > −17), temporarily quiescent systems, crucial for constraining early feedback processes in low-mass galaxies.